Biohydrogen and Biomethane Production from Acid Pretreated Water Hyacinth and Kinetics - Jarusiripot, Chutima; Sungthong, Daoroong (Trends in Sciences, 2022)
In this study, several ratios of water hyacinth to acid solution were varied from 1:10, 1:20, 1:30, and 1:40, in order to find the optimum ratio for biohydrogen and biomethane production. The pretreated water hyacinth was used as substrates to produce hydrogen in the first stage anaerobic digestion. Then the residue from hydrogen production was used as substrate for methane production in the second stage. The results showed that cumulative hydrogen production slightly increased with the substrate to acid solution (2 % v/v H2SO4) ratio. The highest cumulative hydrogen produced (77.47 mL with 7.75 mL H2/gVS) at 1:40 substrate to acid solution, however the highest hydrogen content obtained at 1:20 (40.1 %). Hydrogen could not be produced from water hyacinth without acid pretreatment, only 4 mL hydrogen was detected from control case. In the second stage, methane was generated from the residue of first stage fermentation and found that the highest cumulative methane was obtained from 1:30 substrate to acid solution ratio. The methane content was not significantly different for control (53.68 %), 1:10 (54.45 %), 1:20 (53.46 %), and 1:30 (52.10 %) cases. The modified Gompertz, modified Logistic, and Cone model were best fit models for hydrogen production since the fermentation needed lag phase time before the hydrogen can be generated. The calculated lag phase time from modified Gompertz model increased from 0.0531 to 0.9775 day, and those from modified Logistic model increased from 0.3867 to 1.0305 day. On the other hand, the Cone model, first order model, and Transference function agreed very well with the second stage methane production data where lag phase time was nearly zero. HIGHLIGHTS Biohydrogen cannot be produced from water hyacinth without acid pretreatment The optimum substrate to acid solution ratio for pretreating water hyacinth for hydrogen production is at 1:20 with highest hydrogen content. Higher acid ratio produced more undesired gases Biomethane can be produced from water hyacinth without acid pretreatment. Only mechanical size reductionand heating pretreatment are enough to facilitate the process Hydrogen production were best described by the modified Gompertz, modified Logistic, and Cone model. On the other hand, second stage biomethane production were best described by the Cone model, first order model, and Transference function GRAPHICAL ABSTRACT